For Real Now. (Hoorn : Stichting De Achterstraat, 1990)
Adams, Dennis ; Belcher, Alan ; Bijl, Guillaume ; BP ; Oklahoma, Banco ; Deleu, Luc ; Formalhaut ; Garbelli, Francesco ; Ingold Airlines ; Kozic, Maria ; Leccia, Ange ; Likely, Seymour ; Servaas ; Thorsteinsson, Thorvaldur ; Tempi en Wolf
For Real Now, Korte Achterstraat 2A - Weeshuistuin - V.O.C. Pakhuis - De Boterhal, Kerkplein 39 - Voor Parkschouwburg - Oostereiland - Venidse - Julianapark Hoorn - De Twee Wezen, Westerstraat 109 - Enkhuizen, 1 juli - 9 sept. '90
boek